Analysis of antibiotic use and access to drugs among poultry farmers in Kenya - Muloi, Dishon M.; Kasudi, Mitchelle R.; Murungi, Maurice K.; Ibayi, Eugine L.; Kahariri, S.; Karimi, C.; Korir, Max; Muasa, B.; Mwololo, D.; Ndanyi, R.; Ndungi, R.; Njiru, J.; et al. (Elsevier, 2025)
Understanding access to and use of antibiotics in livestock production systems is critical for guiding antimicrobial stewardship programmes and animal health services. We analysed antibiotic use practices among smallholder-intensive poultry farms in Kenya and characterised access to veterinary supply chains by calculating travel time to drug stores.